Field-scale treatment of landfill gas with a passive methane oxidizing biofilter. Issue 5 (1st September 2008) - Philopoulos, Andrew; Felske, Christian; McCartney, Daryl
Abstract : Municipal solid waste landfills are a major contributor to global methane emissions, a potent greenhouse gas. A treatment alternative was evaluated by installing three biogenic methane oxidizing biofilters into the landfill cover at the Leduc and District Regional Landfill (Alberta). Mature yard-waste compost was used as the biofilter medium. The results, collected over a period of 10 months, showed that two sites performed well as low surface emissions (<15 g CH4 m -2 d -1 ) were observed on 6 of 8 monitoring events. These two sites also demonstrated sufficient temperature (>20 °C) and moisture (>0.25 L L -1 ) levels to support a high level of biogenic activity, the former despite cold winter temperatures (<0 °C). The third site showed low calculated methane influent flows (<5 g CH4 m -2 d -1 ) and therefore observations of performance were limited.